ONE OF THE CONTEMPORARIES OF MAKSUD SHEIKHZADE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
During the  years of her life in Tashkent, Shaikhzoda not only mastered Uzbek, but also wrote poems and articles in this language, translated Pushkin's works, studied Cholpon's work, and lovingly studied Navoi's work.